An Extension of the Guided Wave M‐Component Model Taking Into Account the Presence of a Tall Strike Object. Issue 18 (21st September 2021) - Li, Quanxin; Rachidi, Farhad; Rubinstein, Marcos; Wang, Jianguo; Azadifar, Mohammad; Cai, Li; Wang, Junlin; Zhou, Mi; Fan, Yadong
Abstract: We present in this paper an extension of the guided‐wave M‐component model of Rakov et al. considering the presence of a vertically elevated strike object. The tall object is represented as a lossless, uniform transmission line. Expressions for the current distribution along the channel and along the strike object are derived. Simulation results for the electric field at close (100 m), intermediate (15 km), and far (100 km) distance ranges are presented, considering fast and slow M‐component currents. The results show that, for very tall structures and fast M‐component waves, the presence of a tall strike object can result in a sharp peak superimposed on the M‐component electric field at intermediate and far distance ranges (e.g., 15 and 100 km). At close distances, the electric field of a fast M‐component is characterized by an initial negative excursion followed by a polarity change. It is shown that the presence of the tower results in a decrease of the negative initial excursion of the field. For slow M‐component waveforms or for moderately tall structures, the presence of the tall strike object can be disregarded in the M‐component field calculations. A discussion on the influence of the M‐wave channel height and velocity on the electric fields for fast M‐component currents is also presented. The study suggests a noticeable effect of the M‐wave velocity on the electric fields at all distance ranges. The variations of the wave velocity and channel length affect the time of appearance of the superimposed sharp peak on the electric fields. However, the sharp peak magnitude, which is due to the presence of the tower, is independent of the channel length and wave velocity. It is determined by the injected current and the reflection coefficients from the ground and tower top. Key Points: We propose an extension of the guided‐wave M‐component model of Rakov et al. considering the presence of a vertically elevated strike object For very tall structures and fast M‐component waves, the presence of a tall strike object can result in a sharp peak superimposed on the M‐component electric field at intermediate and far distance ranges The superimposed sharp peak amplitude is independent of the channel length and the wave velocity, while its arrival time is affected by the channel length and the wave velocity